Fluoroscopy-Assisted Stress Testing of the Thumb Metacarpophalangeal Joint to Assess the Ulnar Collateral Ligament. (June 2013) - Patel, Ashish; Patel, Archit; Edelstein, David; Choueka, Jack
Background: Diagnostic stress testing of ulnar collateral ligament (UCL) injuries of the thumb metacarpophalangeal (MCP) joint is pivotal to determining treatment. Comparison to the uninjured extremity and fluoroscopy-assisted examination are readily available modalities in the assessment of these patients, with 5–10° differences impacting treatment. Comparative examination, however, assumes that both extremities are normally equal, which has never been verified experimentally. Comparison of clinical and fluoroscopic examination has also never been scrutinized. Method: One hundred asymptomatic participants underwent both fluoroscopic and traditional stress examinations to determine maximum passive radial deviation at neutral MCP flexion. Results: Absolute clinical vs. fluoroscopic differences demonstrated a significant difference of 5.6° (SD 5.1°). Absolute variability between left-to-right measurements was 4.5° (SD 4.1°) and increased significantly as baseline stress deviation increased ( R = 0.43; p < 0.001). Left-to-right difference exhibited no correlation to age, gender, or BMI. Conclusions: The current investigation demonstrates right–left differences and differences between clinical and fluoroscopic testing of which practitioners should be aware when making treatment decisions for UCL injury of the thumb MCP joint.